Analisis Aset Sustainable Livelihood pada Kelompok Wanita Tani Bina Sejahtera Desa Sindangjawa Kecamatan Dukupuntang Kabupaten Cirebon - Hamdan Hamdani; Anisul Fuad (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
The Women Farmers Group in Sindangjawa Village is one of the village government's efforts in empowering the community through activities in agriculture to meet family food needs and security. The purpose of this research was to determine the sustainable livelihood assets contained in the Women Farmers Group in Sindangjawa Village. The method used in this research is descriptive qualitative with data collection through observation, interviews and documentation. The results show that there are sustainable livelihood assets in the Women Farmers Group in Sindangjawa Village (human capital, natural capital, financial capital, social capital, physical capital). However, these assets have not been fully utilized by the Women Farmers Group in Sindangjawa Village.